Patent Vitello-Intestinal Duct: A Misdiagnosis of Persistent Umbilical Granuloma - Hei Yi Wong; Yuk Kwan Ng; Kin Wai Edwin Chan; Kim Hung Lee (EL-Med-Pub, 2018)
Patent vitello-intestinal duct (VID) is a rare embryological defect. Pre-operative diagnosis may be difficult to be made by primary physicians and misdiagnosed as umbilical granuloma. We report a 24-day-old girl with repeated attempts of silk-tie ligation in primary care as she presented with a persistent umbilical mass with discharge. On referral to tertiary pediatric surgical center, diagnosis of patent VID was made, and umbilical exploration with bowel resection was performed. The patient was asymptomatic after the definitive surgery.